'We recommend compliance': bargaining and leverage in Ethiopian–US intelligence cooperation. Issue 153 (3rd July 2017) - Odinga, Sobukwe
ABSTRACT: Disputes over the costs and benefits of intelligence liaisons between the US and its African allies are routine. The contentious and largely overlooked bargaining processes that stem from these disputes call into question prominent depictions of US–African security partnerships as rigidly hierarchical alliances. Through an assessment of compliance bargaining between Ethiopia and the US over the terms of their intelligence liaison, this article posits that, despite the vast power asymmetry between these allies, Ethiopia routinely dictated and policed the terms of this liaison, while consistently leveraging it as means to acquire political concessions from the US.